1988
DOI: 10.1021/jm00119a016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cognition-activating properties of some mono- and bicyclic lactam derivatives

Abstract: Upon reductive cyclization cyano esters 2, 3, and 9 yielded piperidones and perhydropyrrolo[3,4-c]pyridine lactams, generally as a mixture of diasteromeric cis-trans forms. X-ray crystallographic analyses were carried out on bicyclic dilactam derivatives 6 and 10, and a cis configuration at the ring junction was determined in both cases. A series of neuropsychopharmacological tests performed on the title compounds indicated that they are generally nontoxic even at high doses (up to 1000 mg/kg ip). The cognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…It should be noted that hydrogenated pyrrolo [3,4-c]pyridine core is an important scaffold since compounds of this class possess antibacterial 32 , and anticancer activity 33,34 as well as cognition activating properties. 35 The structures of compounds 7a-e were confirmed by NMR-spectroscopy and HRMS data, as well as X-ray diffraction study (for compounds 7a,b,e). It was found that addition of two molecules of the dipole occurs from the opposite sides of the pyridine ring.…”
Section: Scheme 4 [3+2]-cycloaddition Of N-methyl Azomethine Ylide Tmentioning
confidence: 79%
“…It should be noted that hydrogenated pyrrolo [3,4-c]pyridine core is an important scaffold since compounds of this class possess antibacterial 32 , and anticancer activity 33,34 as well as cognition activating properties. 35 The structures of compounds 7a-e were confirmed by NMR-spectroscopy and HRMS data, as well as X-ray diffraction study (for compounds 7a,b,e). It was found that addition of two molecules of the dipole occurs from the opposite sides of the pyridine ring.…”
Section: Scheme 4 [3+2]-cycloaddition Of N-methyl Azomethine Ylide Tmentioning
confidence: 79%
“…In [2], the reductive cyclization reaction was conducted under hydrogen at 100 °C and 100 atm pressure for 48h by one-pot method. We have the work coming from two steps: the reductive experiment should be made under hydrogen at 60°C and 45 atm pressure for 12 h and after filtration and stripping of the solvent, the final cyclization step was conducted in toluene at 120°C in the same autoclave to avoid high pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The cognition activating properties of cis-perhydropyrrolo [3,4-c]pyridine-3,4-dione was evaluated in enhancing retention for passive avoidance learning in rats. It was also found to be more potent than piracetam in the amnesiareversal testing [2].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the vast majority of the active compounds conserve the 2-oxopyrrolidine ring. This ring has been successfully substituted in almost every position, but compounds where the pyrrolidine ring has been condensed with other rings are rare [110,111].…”
Section: Classification Of Nootropicsmentioning
confidence: 99%